Penerapan Multi-Criteria Decision Making (MCDM) Menggunakan Metode WASPAS Pada Penilaian Kinerja Karyawan Terbaik - Ari Syaripudin; Yasin Efendi; Harriansyah Harriansyah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
The process of evaluating employee performance is an important part of resource management, because employee performance appraisal can be used by decision makers in determining policies. Evaluation of employees usually uses a conventional method, which is determined based on an assessment of attendance, responsibility, and communication. So that the assessment process is still considered inappropriate and requires a long time in determining employee performance. The purpose of this study is to create a decision support system for evaluating the best employee performance using the Multi-Criteria Decision Making (MCDM) model using the Weighted Aggregated Sum Product Assessment (WASPAS) method. The results of the best employee performance assessment from the results of employee calculations with the name Hendri Oktavian get a final total value of 3.32352571 and get the 1st rank as the best employee, an employee with the name Fenny Sari gets a final total score of 3.27544199 and gets a rank 2 employee, and an employee with the name Dara Sagita got a total final score of 3.27102047 and was ranked 3rd best employee